Liberating the Issue of Present Days. About the Foucaltian Critics of Inflationary Speeches on the Present as “Mass Society” and “Estatalized Space” (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
With this article we pretend to contribute, in a really modest way, to the liberation of a tenacious image of our society: which operates as an ideological basis of a group of current socio-political pseudocritics, with great success and diffusion. For this we will undertake the exposition and the analysis of the development group of Naissance de la biopolitique in which Foucault accomplishes the critic of all that number of inflationary speeches that represent our society like a “mass society” and a “estatalized space”. Facing these vague and disproportionate forms of consideration, the foucaltian critic, in its exquisite attention to what happens nowadays, it should reveal how our societies function as systems that optimize the difference –radically nominalists-, in which it is produced, beyond any phantasmatic of the oppressor and invasive estate, a regretion of the legal-estate structures that articulate the socio-politic groups, in benefit of the reconstitution and the social tissue as a communitarian network, suitable for the dynamics of market competence that characterise our enterprise societies. That will open to a new idea of the critic, and to a displacement of its object and objectives.